Phage Therapy -- Everything Old Is New again - Andrew M Kropinski (Canadian Journal of Infectious Diseases and Medical Microbiology)
The study of bacterial viruses (bacteriophages or phages) proved pivotal in the nascence of the disciplines of molecular biology and microbial genetics, providing important information on the central processes of the bacterial cell (DNA replication, transcription and translation) and on how DNA can be transferred from one cell to another. As a result of the pioneering genetics studies and modern genomics, it is now known that phages have contributed to the evolution of the microbial cell and to its pathogenic potential. Because of their ability to transmit genes, phages have been exploited to develop cloning vector systems. They also provide a plethora of enzymes for the modern molecular biologist. Until the introduction of antibiotics, phages were used to treat bacterial infections (with variable success). Western science is now having to re-evaluate the application of phage therapy -- a therapeutic modality that never went out of vogue in Eastern Europe -- because of the emergence of an alarming number of antibiotic-resistant bacteria. The present article introduces the reader to phage biology, and the benefits and pitfalls of phage therapy in humans and animals.